Serum levels of IFN-γ and IL-4 in hospitalised COVID-19 patients – evidence of reduced cytokine storm in discharged patients - Arinola Olatunbosun, Ganiyu; Onifade, Abdulfattah Adekunle; Adigun, Kehinde; Oshingbesan, Mosunmade Babatunde (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Coronavirus disease 2019 is characterised by cytokine storm and it was managed with repurposed drugs, however the effect of this treatment on cytokine storm is unknown. The aim of the study was to investigate the effect of repurposed management on serum Th1 pro-inflammation cytokine (IFN-γ) and Th2 anti-inflammation cytokine (IL-4) in COVID-19 patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The levels of IFN-γ and IL-4 were determined in sera from 45 COVID-19 patients at admission followed-up till discharge after repurposed treatment using ELISA. The mean levels and proportions above normal reference ranges of IFN-γ and IL-4 were compared in COVID-19 at admission and discharge. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The mean values of IFN-γ and IL-4 were significantly higher in COVID-19 patients at admission compared with discharged COVID-19 patients whereas IFN-γ:IL-4 ratio was significantly higher in discharged COVID-19 patients compared with admitted COVID-19 patients. Significantly higher proportion of COVID-19 patients at discharge had IFN-γ within the normal reference ranges compared with COVID-19 patients at admission whereas the proportions of COVID-19 patients at discharge and COVID-19 patients at admission having IL-4 within the normal reference ranges were the same. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Cytokine storm was evidenced in COVID-19 patients at admission and repurposed treatment suppressed pro-inflammation cytokine (IFN-γ) in most discharged COVID-19 patients.